Influence of Transformation Demographic Model on Economic Development of Russia - Maria Kopeykina (European Regional Science Association (ERSA), 2005)
The page represents model of influence of the occurred demographic changes on economic development of Russia. Transformation of model birth rate in modern Russia and its rapprochement to type of the western countries (Austria, Germany, Italy, Spain). Reflection of a social and economic conjuncture in a channel of "the second demographic transition" to which all advanced countries follow. Russia has followed the road long-term changes of economic and demographic model, and return to former models is hardly possible. As a core of the newest tendencies of economic development search of optimum model of life cycle of the person adequate to realities of modern life, among which high requirements to formation and a level of a material well-being acts.
Keywords: 330